Assessment of risks to human health associated with meat from different value chains in Nigeria: Using the example of the beef value chain - Okike, Iheanacho; Grace, Delia; Hussni, M.; Dipeolu, M.; Poole, Elizabeth J.; Gachohi, John; Baker, Derek; Lore, Tezira A.; Rushton, J.; Makita, Kohei (International Livestock Research Institute, 2011)
The study built on a series of logical steps starting with a stakeholders’ workshop which was followed by an extensive review of available literature on key meat-borne hazards in Nigeria; with both activities indicating greater concern over the risk of consuming contaminated beef. Beef value chain and hospital surveys were then conducted for hazard identification, understanding the socioeconomic aspects of beef safety and determining costs associated with treatment of diarrhoea. Information from these primary and secondary sources fed into the quantitative risk assessment (QRA) model to estimate the risk of illness associated with the consumption of contaminated beef by people differentiated by sex, age class and health status. Finally and based on inputs from the foregoing, the cost of treatment and lost productivity was estimated using Monte Carlo stochastic simulation to take into account uncertainty and variability that might have been introduced by the quality of data. We then used data from the Global Burden of Disease (GBD) to estimate additional costs from loss of statistical lives based on the concept of Disability-adjusted life years (DALY).The study estimated the total cost associated with food-borne diarrhoea at US$3.6 billion; and the cost associated with beef-borne diarrhoea at US$156 million. DALY lost from diarrhoea are estimated at 67,712, corresponding to a statistical value of US$2.7 billion; while the DALYs lost from beef-associated disease correspond to 13,542 with a statistical value of US$542 million. We discuss the other aspects of cost of beef-borne illness which were not captured because of inadequate data but which are likely to be similar or greater to the costs calculated. Chronic and non-gastrointestinal illness associated with food-borne disease is less common than gastrointestinal illness but more severe, and experts consider it to have an equivalent cost. Other costs of beef-borne disease, which were not quantified, include reduced animal productivity, costs of control and trade impacts. This initial estimate suggests beef-borne disease is costing Nigeria US$854 million per year. Furthermore, a reduction of between 20-70% in beef-borne disease is feasible. Recommendations are then given on risk-based approaches for reducing beef-borne disease in Nigeria.